From Theory to Practice: Bone Health in Women with Early Breast Cancer Treated with Aromatase Inhibitors - Leonor Vasconcelos de Matos; Leonor Fernandes; Maria Teresa Neves; Fátima Alves; Mafalda Baleiras; André Ferreira; Pedro Giesteira Cotovio; Tiago Dias Domingues; Mariana Malheiro; Ana Plácido; Maria Helena Miranda; Ana Martins (Current Oncology, 2021)
Aromatase inhibitors (AI) are extensively used as adjuvant endocrine therapy in post-menopausal women with hormone receptor-positive early breast cancer (HR+ EBC), but their impact on bone health is not negligible. This work aimed to assess bone loss, fracture incidence, and risk factors associated with these events, as well as the prognostic influence of fractures. We have conducted a retrospective cohort study of women with HR+ EBC under adjuvant therapy with AI, during a 3-year period. Four-hundred-and-fifty-one eligible women were reviewed (median age 68 years). Median time under AI was 40 months. A fracture event occurred in 8.4%, mostly in the radium and femoral neck and in older women (mean 74 vs. 68 years, p = 0.006). Age (OR 1.01, 95% CI 1.01–1.07, p = 0.024) and time under AI (OR 1.02, 95% CI 1.00–1.04, p = 0.037) were independent predictors of fracture, with a fair discrimination (AUC 0.71). Analysis of disease-free survival according to fracture event varied between groups, disfavoring the fracture cohort (at 73 months, survival 78.6%, 95% CI, 47.6–92.4 vs. 95.6%, 95% CI, 91.2–97.8, p = 0.027). The multivariate model confirmed the prognostic impact of fracture occurrence (adjusted HR of 3.17, 95% CI 1.10–9.11; p = 0.032). Bone health is often forgotten, despite its great impact in survivorship. Our results validate the pathophysiologic link between EBC and bone metabolism, which translates into EBC recurrence. Further research in this area may help refine these findings. Moreover, early identification of women at higher risk for fractures is warranted.